Reversible cerebral vasoconstriction syndrome following intracranial hypotension in a postpartum patient: a case report and literature review - Li, Shuhua; Yang, Yi; Zuo, Jiacai; Du, Ningli; Kou, Guoxian (Frontiers in Neurology, 2023)
Introduction Reversible cerebral vasoconstriction syndrome (RCVS) is a potentially life-threatening neurological disorder, rarely linked to intracranial hypotension. The presentation showed a patient with intracranial hypotension after peridural anesthesia who experienced RCVS during the early postpartum period, suggesting a potential involvement of intracranial hypotension in RCVS occurrence. Case report A young female of 29 years of age initially developed an orthostatic headache after undergoing a painless delivery with lumbar epidural anesthesia. Intracranial hypotension was considered the underlying cause. Her headache was partially resolved after intravenous fluid therapy and strict bed rest. After 2 days, the patient had a new onset thunderclap headache with generalized seizures, cortical blindness, and elevated blood pressure. An MRI scan revealed high signal intensity within the temporal, parietal, and occipital lobes, left caudate nucleus, and right cerebellum on T2-FLAIR imaging with vasogenic edema. MR angiography indicated multifocal, segmental, diffuse narrowing affecting the cerebral arteries that are large and medium. An RCVS2 score was six, and the patient was diagnosed with RCVS. She was managed conservatively, quickly improving her symptoms. After 10 days, a follow-up MRI indicated a significant reduction in the abnormal signal, and a substantial resolution of the constriction of the cerebral artery constriction was confirmed by MR angiography. Conclusion Intracranial hypotension could potentially lead to RCVS in postpartum patients, and it may be triggered by cerebral vasospasm secondary to intracranial hypotension.